Ceramic bearings for total hip arthroplasty are associated with a reduced risk of revision for infection. Issue 3 (May 2018) - Madanat, Rami; Laaksonen, Inari; Graves, Stephen E; Lorimer, Michelle; Muratoglu, Orhun; Malchau, Henrik
Introduction: Periprosthetic joint infection (PJI) is a serious complication after total hip arthroplasty (THA) and bearing material's associations to PJI prevalence is largely unknown. The main purposes of this study were to determine if revision for infection varied depending on the type of bearing surface used in primary THA and to study whether patient or implant related factors had an effect on this variation. Methods: A total of 177, 237 primary THA procedures from the Australian Registry (AOANJRR) were analysed. 3 bearing surfaces were compared. Metal-on-highly cross-linked polyethylene (MoXP) bearing had been used in 95, 129 hips, ceramic-on-highly cross-linked polyethylene (CoXP) in 24, 269 hips, and ceramic-on-ceramic (CoC) in 57, 839 hips. Revision rates for infection were compared between the 3 groups. Results: Both MoXP and CoXP had a higher revision rate for infection compared to CoC hips (hazard ratio [HR] 1.46 (1.25, 1.72), p < 0.001) and HR 1.42 (1.15, 1.75), p = 0.001 respectively). Patients aged 70 years or less had a lower revision rate for infection when a CoC bearing was used. This difference was independent of sex, and prostheses selection. No difference was evident if the femoral component was cemented or a head size of 28 mm was used. Discussion: In this registry-based material, use of a CoC bearing was associated with a lower risk of revision for infection in patients younger than 70 years when cementless femoral components were used. Further studies are needed to verify this finding.